2018
DOI: 10.1007/s00109-018-1627-8
|View full text |Cite
|
Sign up to set email alerts
|

AMPKα inactivation destabilizes atherosclerotic plaque in streptozotocin-induced diabetic mice through AP-2α/miRNA-124 axis

Abstract: Hyperglycemia reduced collagen synthesis, leading to the formation of unstable atherosclerotic plaque induced by collar placement around carotid in apolipoprotein E knockout mice. Hyperglycemia destabilizes atherosclerotic plaque in vivo through an AMPKα/AP-2α/miRNA-124/P4Hα1-dependent collagen synthesis. Metformin functions as a stabilizer of atherosclerotic plaque to reduce acute coronary accent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 34 publications
1
50
0
Order By: Relevance
“…37 Metformin, as an antidietetic drug by activating AMPK, inhibits inflammation induced by LPS in vascular cells. 23,24 In lung, suppressing AMPK aggravates LPS-induced lung injury, hypoxia-induced pulmonary arterial hypertension and endothelial barrier dysfunction. 24 Considering these results, it is out of question that AMPK plays a crucial role in VitB6-inhibited inflammation in macrophage.…”
Section: Discussionmentioning
confidence: 99%
“…37 Metformin, as an antidietetic drug by activating AMPK, inhibits inflammation induced by LPS in vascular cells. 23,24 In lung, suppressing AMPK aggravates LPS-induced lung injury, hypoxia-induced pulmonary arterial hypertension and endothelial barrier dysfunction. 24 Considering these results, it is out of question that AMPK plays a crucial role in VitB6-inhibited inflammation in macrophage.…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNA is a kind of small, nonprotein‐coding RNA that binds to specific 3′ untranslated regions (3′‐UTR) of mRNA and represses target gene expression through inhibition of translation or transcript degradation . In vascular cells, several microRNAs, such as miR‐126, miR‐217, miR‐10a, miR‐124, etc., have been identified to regulate multiple cellular functions including the glucose and lipid metabolisms, senescence and blood flow . We have previously reported that miR‐15b‐5p regulates collateral artery formation by targeting protein kinase B in endothelial cells and miR‐199 regulates normalise arachidonic acid metabolism in nitrate tolerance by prostaglandin synthase .…”
Section: Introductionmentioning
confidence: 99%
“…5 In vascular cells, several microRNAs, such as miR-126, miR-217, miR-10a, miR-124, etc., have been identified to regulate multiple cellular functions including the glucose and lipid metabolisms, senescence and blood flow. [6][7][8][9] We have previously reported that miR-15b-5p regulates collateral artery formation by targeting protein kinase B in endothelial cells and miR-199 regulates normalise arachidonic acid metabolism in nitrate tolerance by prostaglandin synthase. 10,11 Interestingly, endogenous expressions of miR-133a and miR-130, are null or very low in quiescent endothelial cells, while their expressions are ectopically induced by risk factors, resulting in endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…AMPK, as a regulator/modulator of redox status in vascular cells, 36,37 has been reported to inhibited GTPCH1 protein degradation in endothelial cells. We thought that AMP-activated protein kinase (AMPK) should play an important role in this biological process.…”
Section: Discussionmentioning
confidence: 99%